If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + -5y = 41 + -6x Solving 3x + -5y = 41 + -6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '6x' to each side of the equation. 3x + 6x + -5y = 41 + -6x + 6x Combine like terms: 3x + 6x = 9x 9x + -5y = 41 + -6x + 6x Combine like terms: -6x + 6x = 0 9x + -5y = 41 + 0 9x + -5y = 41 Add '5y' to each side of the equation. 9x + -5y + 5y = 41 + 5y Combine like terms: -5y + 5y = 0 9x + 0 = 41 + 5y 9x = 41 + 5y Divide each side by '9'. x = 4.555555556 + 0.5555555556y Simplifying x = 4.555555556 + 0.5555555556y
| x^2-4x+11=0 | | s+1.5=0.8 | | 3(v-1)=6v-4 | | B(12+b)-7=2b+b(-4+b) | | 13x*2+5x+1=0 | | 2x+5-x=9-x+2 | | 1=0.4-0.6x-5 | | -8*-3+3*4= | | 2-3y=-8 | | -9(x-2)=-10x | | 31-17= | | 5x-18-4*x=-36 | | -9(x-2)+18=-10x | | -(3y-6)+10= | | 4+2(-x+2)=26 | | 25.33*x+.5*(-7.5)*x^2=4.4*x | | f+4/8=6 | | 13=4x+3(x-5) | | 4*7+9*-2= | | 6(3x-1)-18= | | 4c+21c+27=0 | | 3(9a+4b)-8(a+8b)=0 | | -5(4q+2)=-3q+10 | | r=-20+10a | | -3*-8-9= | | 3=4(x+3)-5 | | -79+12x=38+3x | | 9y-9=9y-y | | 44-3x=15x+16 | | 2(5-4)= | | (2-5)= | | 7*-2+3= |